Application of cooling, heating loads in an autonomous microgrid as a control strategy - Vahedipour Dahraie, Mostafa; Rashidizadeh Kermani, Homa; Najafi, Hamid Reza (International Journal of Engineering and Technology, 2015)
In this paper, a control scheme is proposed for a microgrid. In the proposed scheme, by controlling cooling, heating loads (C/H loads), balance between generation and consumption power is kept, and the frequency remains within its nominal value. Application of storage systems imposes costs, operating and maintenance problems to the microgrid owners. Moreover, the charge and discharge process of batteries causes reduction in their lives time. The dominant concept of this scheme is to control frequency without any storage. In this case, the coincidence of generation and consumption in C/H load technology is not necessary. This control system changes the consumption power of C/H loads and responses to unbalance power of microgrid, fast. Moreover, two indices are defined to assess the performance of the microgrid.